HUBUNGAN ANTARA KADAR HIGH SENSITIVE-C REACTIVE PROTEIN DENGAN DERAJAT ASMA BRONKIAL AKUT - Jaya Santika, I Wayan Agus; Suryana, Ketut (journal of internal medicine, 2012)
Bronchial asthma is a chronic inß ammation in the air way. There are some element of cell and cell also to intervention in the inß ammation process. Chronic inß ammation has caused hyper responsiveness in air way, which is episodic attack sign, like wheezing, cough, shortness of breath usually in the night. C-reactive protein is one of the protein which changes in acute infection and acute inß ammation. C-reactive protein is a acute phase response protein which responsibility to defense mechanism. Acute phase protein produced induction by injury or infection. Acute phase reactant synthesis by liver which induction by cytokine like IL-6. In acute asthma attack produced some cytokine pro inß ammatory like IL-1, IL-6 and TNF. All of that cytokine induced liver to produced CRP. Aim for this study, to know the level hs-CRP in asthma attack patient and also to know correlation between the severity of asthma attack and level of hs-CRP in patient who treated in Sanglah General Hospital. This study was enrolling 53 patient acute asthma attack, cross sectional study. All the data collected by interview, physical examination, blood examination which cbc, hs-CRP, also with peak ß ow meter. The data analyzed by SPSS. And the result is the median of level hs-CRP is 7.3 mg/l, and the correlation in odd ratio (OR) is 3.73; CI 95% (1.66 ! 8.41). Based on this study we have the conclusion there strong correlation between level of hs-CRP and severity of asthma attack.
Keywords: Acute asthma attack, hs-CRP, inß ammation